Substrate Integrated Waveguide Based Bandpass Filter with Defected Ground Structure for FMCW Radar Application - Mahant, Keyur; Mewada, Hiren (International Journal of Sensors Wireless Communications and Control, 2020)
Aims: Substrate Integrated Waveguide (SIW) based bandpass filter is presented in this paper. Objectives: In the proposed design, bandpass response is achieved by combining SIW structure with elliptic shaped Defected Ground Structure (DGS) cells. Methods: Simulation of the proposed structure is carried out using commercial software Ansoft High Frequency Structure Simulator (HFSS), which is a three-dimensional frequency domain electromagnetic solver based on the Finite Element Method (FEM). Analysis of three different types of DGS cells including rectangular, circular and elliptical has been carried out. Moreover, Frequency tuning is also carried out by changing the dimension of DGS. Result: Proposed filter is fabricated on the dielectric material RT duroid 5880 with the dielectric constant εr=2.2, dissipation factor tanδ=4 x 10-4 and height h= 0.508 mm. The measured return loss of 25.71 dB and insertion loss of 1.24 dB with 3 dB Fractional Bandwidth (FBW) of 4.8% at the center frequency of 7 GHz. Conclusion: Good agreements are observed between the experimental results and the simulations.
Keywords: High Frequency Structure Simulator (HFSS)